Castle Camus, Isle of Skye: buildings, materials and radiocarbon analysis in the borderlands of medieval Sleat - Thacker, Mark (Proceedings of the Society of Antiquaries of Scotland, 2020)
A study of Castle Camus is presented from the pilot phase of the Scottish Medieval Castles and Chapels C14 Project (SMCCCP). The study highlights various challenges faced by investigators seeking to interpret medieval sites where contemporary documentary evidence is late and the physical upstanding remains are fragmentary. Informed by a wider programme of buildings and materials analysis, the paper presents the first independent dating evidence relating to the construction of Castle Camus, through radiocarbon analysis of an assemblage of wood-charcoal Mortar-Entrapped Relict Limekiln Fuel (MERLF) fragments. This data is consistent with later traditions, reporting that a MacLeod clan chieftain died at the castle site in the very early 15th century, and suggests Castle Camus was the formal administrative centre of the lordship of Sleat throughout the later medieval period. Bayesian techniques are used to correlate these different types of evidence and generate an estimate for the constructional chronology of the earliest upstanding structure. The study suggests that construction of the south-east range at Castle Camus was completed in 1280–1330 cal AD (74.2% probability) or 1365–1400 cal AD (21.2% probability). Further discussion highlights the landscape context of the castle site; with a focus on woodland resources and socially constructed boundaries. Canmore ID 11544